Development of novel fortified beef patties with added functional protein ingredients for the elderly. (December 2016) - Baugreet, Sephora; Kerry, Joseph P.; Botineştean, C.; Allen, Paul; Hamill, Ruth M.
Abstract: The effects of clean label functional protein ingredients; pea protein isolate (PPI), rice protein (RP) and lentil flour (LF), at 3% and 7% inclusion levels on technological and shelf life parameters of beef patties were evaluated over 12 days. Protein content in the RP7 treatment was higher ( P < 0.05) than controls, but did not differ significantly from PPI7 and RP3. No effects on moisture, fat or ash content were detected. LF addition reduced product hardness, cohesiveness, gumminess and chewiness compared with controls. RP-enriched and control patties were associated with lower lipid oxidation over storage than PPI- and LF-enriched patties. RP had a differential effect on (L*), (a*) and (b*) when compared with controls. Microbiological characteristics for all treatments were acceptable after 12 days. Protein fortified beef patties with a softer texture and acceptable technological properties targeted for ease of consumption by older adults were produced in an attempt to reach dietary targeted protein requirements for this segment. Highlights: The potential of PPI, RP and LF as clean label ingredients for enhancing protein content in beef patties were evaluated. Beef patties enriched with rice protein at 7% increased protein. Redness values remained stable in rice protein-enriched patties. Addition of plant proteins had significant and variable effects on texture characteristics.